Effect of granular characteristics on the viscoelastic and mechanical properties of native chestnut starch (Castanea sativa Mill). (October 2015) - Lemos, André M.; Abraão, Ana S.; Cruz, Bruno R.; Morgado, Maria Luísa; Rebelo, Magda; Nunes, Fernando M.
Abstract: Chestnut starch ( Castanea sativa Mill) gels from two cultivars, Longal and Lada, showed different mechanical and rheological properties, being dependent on aging temperature. Gels were more elastic at 5 °C evidenced by the higher intensity of relaxation spectra showing a slower relaxation process. Shape of the relaxation spectra was almost insensitive to aging temperature suggesting a similar interaction at the two temperatures. Lada gels had the lowest equilibrium modulus indicating a more fragile gel in the presence of shear disturbances. Under uniaxial compression Longal gels were the most deformable before fracture and yield higher apparent Young modulus showing also a higher firmness. Both starches contained a similar amylose content but amylose leached from Longal presented a higher molecular weight being this the determinant factor for explaining the differences in viscosity, gel firmness and cold past viscosity. Longal starch presented lower gelatinization temperature range, higher peak height index, amylopectin molecular weight and degree of external organization of starch granules suggesting a more rigid swollen starch granules that contribute to the reinforcement of Longal gels. Longal amylopectin structural features such as higher abundance of short chains might explain the higher breakdown during pasting and lower gelatinization temperature. Lada higher gelatinization temperature range is in line with a higher diversity of cluster with different double helix stabilities that can be due to the heterogeneity of the side chains involved in the double helixes. Results indicate that granule properties play an important role during gelation of chestnut starch and impact on their rheological and mechanical properties. Graphical abstract: Highlights: Chestnut starch gels from two cultivars showed different rheological properties. Shape of the relaxation spectra was almost insensitive to aging temperature. Lada gels had the lowest equilibrium modulus indicating a more fragile gel. Longal gels were the most deformable before fracture and showing a higher firmness.